Tertiary phosphorus removal from wastewater. - Murujew, Olga (Cranfield University, 2019)
To protect surface water bodies, final effluents of wastewater treatment works are being regulated with stricter consents. Phosphorus has been identified as a priority compound and according to the Water Framework Directive its levels in wastewater effluents need to be below 1 mg P/L and in some cases as low as 0.1 mg P/L. To meet these consents efficiently and economically, there are several novel or established tertiary P removal technologies. Chemical P removal is a conventionally applied process. Yet, it requires optimisation in chemical doses and the most appropriate solids liquid separation for tertiary P removal needs yet to be identified to meet the new stricter consents sustainably. Novel tertiary P removal technologies such as immobilised algae beads systems or reactive media constructed wetlands provide a more sustainable approach with no direct use of chemicals on site and the recycling of materials such as the media in the wetland or through conversion of the algal biomass to energy. However, these technologies are not yet fully established and require validation of their viability and cost competitiveness. In this thesis, tertiary P removal technologies have been evaluated with the aim to resolve existing bottlenecks that are associated with the implementation of these technologies when meeting sub 1 mg P/L levels. Three coagulation-based technologies that have not been operated previously in the UK were assessed on their robustness and resilience under steady-state and dynamic conditions against a 0.3 mg P/L target. It was found that ballasted coagulation was the most robust and could consistently deliver effluent concentrations as low as 0.1 mg P/L. Pile cloth media filtration and ultrafiltration were shown to be less robust yet effective at reaching 0.3 and 0.5 mg P/L targets, respectively. The importance of the solid liquid separation step as well as optimisation of dosing and coagulation- flocculation was highlighted. Further it was found that in a ballasted coagulation system, weaker and bigger flocs are generated through the addition of polymer which are efficiently separated through the incorporation of a ballasting agent. Ultimately, guidance on suitable choice of polymers and their doses was given as anionic polymers at doses as low as 0.1 mg/L. From the novel alternatives, a reactive media (steel slag) constructed wetland was operated at full-scale under real conditions and has reached the highest reported P retention capacity to date with very low P effluent concentrations (<1 mg/L from an average of about 8 mg/L) achieved in the first year of operation. During the life cycle of the wetland, P removal decreased substantially, and it was highlighted that the underlying mechanisms are more complex than previously assumed. To address the bottleneck of high costs of beads production in immobilised algae systems, a proof-of-concept has been given where 69.1% alginate recovery was achieved, and algae beads made from recycled alginate were further reused in P removal trials. Ultimately, a cost reduction of 34% of operational costs could be achieved. Finally, the insights were translated into a P removal strategy where the most suitable technologies are recommended for differently scaled wastewater treatment works (WWTW) and different effluent P targets based on their performance, costs and sustainability. For large WWTW, ballasted coagulation appeared to be the most suitable technology while for small WWTW pile cloth media filtration is recommended. Based on this research, ultrafiltration cannot be recommended for tertiary P removal. The novel technologies were highlighted as more sustainable options for small WWTW which still need further understanding and development.
Keywords: P removal; coagulation; steel slag; alginate recovery; pile cloth media filtration; ultrafiltration